MACROPRUDENTIAL AND MICROPRUDENTIAL POLICY IN THE PERSPECTIVE OF LAW NUMBER 21 OF 2011 - Anita Christiani; Rendhy Oktovianus Lisai (Justitia et Pax, 2019)
The establishment of FSA has brought about the consequences of macroprudential policies which are still under the authority of Bank Indonesia while the microprudential  policies have been the Auhtority of FSA. The problem in this study is what the appropriate definition, characteristics and coverage of macroprudential and microprudential supervision regulatory authority are in order to support the economic stability of a country. This type of research was a normative study. The results showed that the definition of macroprudential regulation and supervision policy is the authority given to Bank Indonesia to conduct regulation and supervision of banking institutions out of the institution and health fields, prudential aspect, and bank examination. The characteristics of microprudential and macroprudential banking regulation and supervision can be seen from the policy focus.